Reinforcement of the Papuan Traditional Communal Rights for the Control of Land and Natural Resources - Alwiyah Sakti Ramdhon Syah Rakia (Теоретическая и прикладная юриспруденция)
The ulayat rights of Papuan customary law communities over control of land and natural resources are rights granted by laws and regulations with a number of special powers. This study aims to analyze and provide a conception of strengthening the customary rights of the Papuan customary law community to control over land and natural resources. This research method uses a normative-juridical legal research type, which refers to the legal norms of legislation (statute approach), as well as legal theories and principles as supporters. This research is descriptiveanalytical, using qualitative analysis methods. The results of this study indicate that although the regulation of the customary rights of the Papuan customary law community has been in place for a long time, there are some basic things that need to be considered. Several regulations in the Perdasus do not represent the Papua Special Autonomy Law and tend to be contradictory. These provisions raise a number of problems for the Papuan indigenous peoples with regard to land ownership and the use of natural resources.